Brasil--Nunca Mais reel guide - Simon, James, 1970- (The Center, 2001)
Reel guide to Brasil--Nunca Mais Project microfilm set which includes previously unpublished Supreme Military Court records of political trials in Brazil from approx. 1964-1979 plus supplemental material.